A review of the Murina cyclotis complex (Chiroptera: Vespertilionidae) with descriptions of a new species and subspecies - Pipat, S.; Sunate, K.; Chutamas, S.; Vu Dinh, T.; Khan, F. A.; Ibnu, M.; Gabor, C.; Neil, F.; Bandana, A.; Bates, P.J.J (Museum and Institute of Zoology, Polish Academy of Sciences, 2013)
Until recently, the taxon Murina cyclotis was considered to be a widespread species, albeit one that exhibited considerable individual, sexual and geographical variation. Subsequently however, it was recognised that this taxon was in fact a complex of species. As such, in 2012, two larger forms were recognised as separate and distinct species, namely: M. peninsularis in the Sunda region and M. fionae in Laos and Vietnam. In the current paper, a new cryptic species of the cyclotis -complex is described from peninsular Thailand based on a combination of external, craniodental and genetic differences. In addition, the population previously referred to M. cyclotis from the Nicobar Islands is described as a new subspecies of this new species. Despite this work and the research of others, the taxonomy of M. cyclotis still requires further study. The description of M. peninsularis is emended and the extensive variation in its morphological characters is addressed. The diagnostic characters of each taxon, as well as the additional data on ecology, zoogeography, distribution, echolocation and genetics, where available, are summarised and discussed.